Cultural authenticity and purchase intention of Chinese luxury brand logo - Wang, Zheng; Louis Ringah, Kanyan; Musdi, bin Hj Shanat (University of Novi Sad, Faculty of Technical Sciences, 2025)
Chinese domestic luxury brands (CDLBs) increase in both sales and attention in academic research, due to rise of inconspicuousness consumption. However, there is little research on how cultural authenticity in logo influences on purchase intention of CDLBs. Based on signaling theory and power distance belief, this paper investigates this research gap by taking the cultural authenticity as signalling, inconspicuousness and brand trust as evaluation, and purchase intention as outcome. The study also examines the mediating effect of power distance belief between the inconspicuousness and purchase intention. Across three experiments, the researchers collected survey data from 210 individuals who lived in Beijing, Shanghai, Guangzhou, Shenzhen and Hangzhou, which are the cities which are ranked as highest luxury consumption cities in China. According to the findings of the study, the impact of cultural authenticity in logo on purchase intention is significant, and this impact is observed both directly and indirectly through the effects of inconspicuousness and brand trust. This study's results offer valuable information on methods to enhance customers' perception of cultural authenticity and increase their intention to purchase for CDLBs.